Fundamentals of management essential concepts and applications - Robbins, Stephen P. 1943- (Pearson/Prentice Hall, 2008)
Principles of Management courses that require a brief and/or skills focused text. Robbins/DeCenzo is the best-selling brief paperback text that gives students more depth and breadth of practical tools to practice their management skills (Management Workshop) than any other textbook.